2020
DOI: 10.47067/reads.v6i2.220
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic and Demographic Factors of Poverty Alleviation in Pakistan: A Case Study of Southern Punjab

Abstract: This study aims to explore the socio-economic and demographic determinants of poverty in Southern Punjab by using the cross sectional data consisting of 785 household heads. Binary logistic regression  and ordinary least square method are used for estimation. The findings exhibit that the variables like family system, household size, presence of disease and status of employment of household head are positively and significantly related to  poverty whereas household head age, rural-to-urban migration,  years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The issue of Households Poverty has been discussion several times with so many socioeconomic variables and few selected studies are given in this section. R. Ahmad and Faridi (2020) analyzed the socio-economic and demographic factors of poverty in Southern Punjab. The study took cross-sectional data consisting of 785 household heads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue of Households Poverty has been discussion several times with so many socioeconomic variables and few selected studies are given in this section. R. Ahmad and Faridi (2020) analyzed the socio-economic and demographic factors of poverty in Southern Punjab. The study took cross-sectional data consisting of 785 household heads.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The certain social and cultural factors are pivotal to address in order to keep maternal mortalities low in country (Winkvist & Akhtar, 2000, Asim et al, 2021Kachoria et al, 2022). Beside that it is a challenging job to work in regions like South Punjab where number of socio-economic and cultural factors make the area underdeveloped (Ahmad & Faridi, 2020). The current research has indicated number of hurdles and challenges in the way of lady health workers which include their low salaries, their fight with social and cultural elements, the harassment, abuse, threat factor and role of health department in different manners in creating awareness on maternal health seeking behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Their results implied that 18% of the households were bearing (MDP) and multidimensional measures were necessary to overcome the said issue. R. Ahmad and Faridi (2020) used cross sectional data for determining the poverty in South Punjab via household survey. Their study was at divisional level and exhibited that households were likely to be poor due to variables such as higher dependency rate due to large household size, unemployed household head and family system.…”
Section: Literature Reviewmentioning
confidence: 99%